2017
DOI: 10.1152/jn.00546.2016
|View full text |Cite
|
Sign up to set email alerts
|

Multidigit force control during unconstrained grasping in response to object perturbations

Abstract: Because of the complex anatomy of the human hand, in the absence of external constraints, a large number of postures and force combinations can be used to attain a stable grasp. Motor synergies provide a viable strategy to solve this problem of motor redundancy. In this study, we exploited the technical advantages of an innovative sensorized object to study unconstrained hand grasping within the theoretical framework of motor synergies. Participants were required to grasp, lift, and hold the sensorized object.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…With the TACtile-sensorized Object (TACO), we are able to record the position and the normal force exerted by each finger on its sensorized surface, while it allows participants to freely choose the position for digit placement on the object, thus enabling unconstrained grasping (Schürmann et al, 2011). For details on using this device for gasping studies, see also Naceri et al (2017). For this study, an additional force/torque sensor was integrated in the center of the TACO to additionally record the net torque and force vectors (see below).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the TACtile-sensorized Object (TACO), we are able to record the position and the normal force exerted by each finger on its sensorized surface, while it allows participants to freely choose the position for digit placement on the object, thus enabling unconstrained grasping (Schürmann et al, 2011). For details on using this device for gasping studies, see also Naceri et al (2017). For this study, an additional force/torque sensor was integrated in the center of the TACO to additionally record the net torque and force vectors (see below).…”
Section: Methodsmentioning
confidence: 99%
“…It is possible to grasp the same object in an infinite number of ways, due to the multiple combinations of digit placement on the object and the level of force exerted by each digit. Grasping and manipulating an object requires that the central nervous system masters this redundancy in degrees of freedom (Bernshtein, 1967;Naceri et al, 2014Naceri et al, , 2017. Sensory feedback from proprioception, touch, and other modalities such as vision plays a key role in the control of grasping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another pivotal role of the sense of touch is the delivery of direct information about surface friction, compliance, and microslip, which are important for dexterous manipulation of objects and grasp control (102,103). Indeed, the tactile channel plays an important role in the control of digit force (104,105) and in the perception, execution and planning of fine hand movements (3). Several studies demonstrated the crucial role of cutaneous information in other motor tasks, such as in the control of grasp and finger posture (106), and guiding hand reaching (5).…”
Section: Figure About Herementioning
confidence: 99%
“…The most significant of them are load cells [ 16 ], strain gauges [ 7 ] piezoresistive sensors, such as Force Sensing Resistor (FSR) sensors [ 13 , 14 ]. Also ad hoc developed sensor modules based on resistive measurements have been used, where the resistance of a conductive elastometer is changed by the applied normal force [ 15 , 17 ]. However, it is shown that the capacitive sensing principle has better performance than other technologies in terms of simple structure, stability and temperature independence [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%